Designers' guide to EN 1992-2 : Eurocode 2, design of concrete structures. Part 2, - Hendy, C. R. (Thomas Telford, 2007)
This guide describes the principles and requirements for safety serviceability and durability of concrete bridges.
At foot of title: Eurocodes Expert.
Keywords: Concrete bridges -- Standards -- Europe.; EN1992 Eurocode 2 (Standard); elektronické knihy; electronic books